Integrating Enterprise Risk Management (ERM) with Knowledge Management (KM) through HSE UTP Lessons Learned System - Samin, Nurul Izzah (UNIVERSITI TEKNOLOGI PETRONAS, 2012)
The complexity of the enterprise risk management is identifying and coordinating risk processes actions across organization. Moreover, risk failures is not being widely disseminated in order to improve practices and tighten policies. The merging of the two disciplines of Knowledge Management (KM) and Enterprise Risk Management (ERM) is foreseen to bring greater value in evaluating and assessing risk. Health Safety and Environment Lessons Learned System (HSELLS) is a project that aims to develop an online, document management application in communicating the risk throughout organization. This paper seeks to contribute to the emergence of research on Enterprise Risk Management by applying KM tool to support risk monitoring and review process. The paper will demonstrates the use of Lessons Learned System as part of KM technology via a case study of HSE UTP, to reduce time, improve decision making, and increase productivity and reliability. A system development life cycle is used to develop HSELLS. At the end of the project, a working prototype is developed to create a platform for user to share and disseminate risk throughout the organization.